Intracochlear Electrocochleography: Response Patterns During Cochlear Implantation and Hearing Preservation. Issue 4 (July 2019) - Giardina, Christopher K.; Brown, Kevin D.; Adunka, Oliver F.; Buchman, Craig A.; Hutson, Kendall A.; Pillsbury, Harold C.; Fitzpatrick, Douglas C.
Abstract : Objectives: Electrocochleography (ECochG) obtained through a cochlear implant (CI) is increasingly being tested as an intraoperative monitor during implantation with the goal of reducing surgical trauma. Reducing trauma should aid in preserving residual hearing and improve speech perception overall. The purpose of this study was to characterize intracochlear ECochG responses throughout insertion in a range of array types and, when applicable, relate these measures to hearing preservation. The ECochG signal in cochlear implant subjects is complex, consisting of hair cell and neural generators with differing distributions depending on the etiology and history of hearing loss. Consequently, a focus was to observe and characterize response changes as an electrode advances. Design: In 36 human subjects, responses to 90 dB nHL tone bursts were recorded both at the round window (RW) and then through the apical contact of the CI as the array advanced into the cochlea. The specific setup used a sterile clip in the surgical field, attached to the ground of the implant with a software-controlled short to the apical contact. The end of the clip was then connected to standard audiometric recording equipment. The stimuli were 500 Hz tone bursts at 90 dB nHL. Audiometry for cases with intended hearing preservation (12/36 subjects) was correlated with intraoperative recordings. Results: Successful intracochlear recordings were obtained in 28 subjects. For the eight unsuccessful cases, the clip introduced excessive line noise, which saturated the amplifier. Among the successful subjects, the initial intracochlear response was a median 5.8 dB larger than the response at the RW. Throughout insertion, modiolar arrays showed median response drops after stylet removal while in lateral wall arrays the maximal median response magnitude was typically at the deepest insertion depth. Four main patterns of response magnitude were seen: increases > 5 dB (12/28), steady responses within 5 dB (4/28), drops > 5 dB (from the initial response) at shallow insertion depths (< 15 mm deep, 7/28), or drops > 5 dB occurring at deeper depths (5/28). Hearing preservation, defined as < 80 dB threshold at 250 Hz, was successful in 9/12 subjects. In these subjects, an intracochlear loss of response magnitude afforded a prediction model with poor sensitivity and specificity, which improved when phase, latency, and proportion of neural components was considered. The change in hearing thresholds across cases was significantly correlated with various measures of the absolute magnitudes of response, including RW response, starting response, maximal response, and final responses (p's < 0.05, minimum of 0.0001 for the maximal response, r's > 0.57, maximum of 0.80 for the maximal response). Conclusions: Monitoring the cochlea with intracochlear ECochG during cochlear implantation is feasible, and patterns of response vary by device type. Changes in magnitude alone did not account for hearing preservation rates, but considerations of phase, latency, and neural contribution can help to interpret the changes seen and improve sensitivity and specificity. The correlation between the absolute magnitude obtained either before or during insertion of the ECochG and the hearing threshold changes suggest that cochlear health, which varies by subject, plays an important role.